Social Isolation, Loneliness, Anxiety, and Quality of Life in a Chronic Ulcer Population With and Without Stigma: An Observational Trial - Teresa J Kelechi PhD, RN; Martina Mueller PhD; Margaret Prentice MBA; Mohan Madisetti MSc (Journal of Patient Experience)
Chronic leg ulcers impact millions worldwide, causing visible symptoms including discoloration, swelling, scarring, and requiring bulky bandaging, which often leads to stigma. Stigma may worsen other psychosocial impairments. This observational study examined stigma, social isolation, loneliness, anxiety, and quality of life (QOL) in adults aged 50+ receiving clinic-based wound care. Participants provided sociodemographic information and completed validated assessments. Among the 26 completers (13 with stigma/S+, 13 without stigma/S-), the average age was 63.2 years; 38% were female, and 58% Black/African American. Most (73%) had ≥high school education, 77% were single, and 42% were employed. Mean BMI was 38.7 kg/m², with 3.7 comorbidities. Stigma scores were higher in S+ (9.8 ± 4.6) versus S- group (6.0 ± 0.0). Loneliness was ≥40 for 15% (S-) versus 53% (S+). Social support was higher in S+ (77.0 ± 21.9) versus S- (64.5 ± 22.3), as was anxiety (50.5 ± 7.6 vs 43.3 ± 8.5). S+ reported lower QOL in appearance (2.8 ± 1.6) and clothing (2.4 ± 1.3). Findings underscore stigma's impact on health, warranting further research on protective and resilience interventions.